Liking and wanting pleasant odors: different effects of repetitive exposure in men and women - Triscoli, Chantal; Croy, Ilona; Olausson, Håkan; Sailer, Uta (Frontiers in Psychology, 2014)
Odors can enrich the perception of our environment and are commonly used to attract people in marketing situations. However, the perception of an odor changes over repetitions. This study investigated whether repetitive exposition to olfactory stimuli leads to a change in the perceived pleasantness (“liking”) or in the wish to be further exposed to the same olfactory stimulus (“wanting”), and whether these two mechanisms show gender differences. Three different pleasant odors were each repeatedly presented for 40 times in random order with a mean inter-stimulus interval of 18 s. Eighteen participants rated both “liking” and “wanting” for each of the 120 olfactory stimuli. Wanting ratings decreased significantly over repetitions in women and men, with a steeper decrease for men during the initial trials before plateauing. In contrast, liking ratings decreased significantly over repetitions only in men, with a steeper decrease after the initial ratings, but not in women. Additionally, women scored higher in a questionnaire on reward responsiveness than men. We conclude that positive evaluation (liking) and the wish to experience more of the same (wanting) are different concepts even in the domain of olfaction. The persistence of perceived pleasantness in women may be due to the attribution of a greater subjective value to odors.